The Implementation of Independent Campus Learning (MBKM) in The Thematic Real Work Lecture (KKNT) at STKIP Al-Amin, Indramayu District: A Case Study of Students 6th Semester of STKIP Al-Amin - Roa, Hidayat (Foreign Language Instruction Probe, 2023)
Research on the implementation of independent learning on an independent campus in thematic real work lectures (KKNT) at STKP Al-Amin Indramayu is a form of appreciation to students who have participated in KKNT activities carried out in 7 villages in Anjatan District, including: 1) Bugis Tua Village, 2) Mangun Jaya Village, 3) Cilandak Lor Village, 4) Lempuyang Village, 5) Anjatan Baru Village, 6) Kopyah Village and 7) Wanguk Village. Then it has implications for whether students in KKNT are indeed carrying out the tridarma of higher education which is based on the spirit of independent campus learning. The method used in this study was qualitative by determining 7 respondents from 7 KKNT workplaces to be able to find out an overview of the implementation of KKNT in each village where students were sent for job training. Students who carry out KKNT activities are very enthusiastic about these activities and hope that in the next time the committee will be even better in preparing for the implementation of KKNT. Students are well received in their place in the village and carry out activities that are usually carried out by the community there, such as helping to teach in schools, teaching salaries, collaborating in sports, and so on. However, there has been no working group that has plunged into the potential of the village, namely agriculture. Success in the implementation of KKNT in Anjatan District will be better if it is based on careful preparation, complete debriefing, and adequate monitoring. Because indeed students are still learning how to interact and realize programs in the community in a real way.